Effect of clearance height on tip leakage flow reduced by a honeycomb tip in a turbine cascade. (August 2019) - Chen, Fu; Fu, Yunfeng; Yu, Jianyang; Song, Yanping
In this paper, the control mechanism of the honeycomb tip structure on the tip leakage flow of a turbine cascade is studied experimentally and numerically, and the sensitivity of tip leakage flow characteristics to different clearance heights from 0.5% to 2% based on the blade span are mainly discussed. A flat tip is considered as a comparative case. The results show that a part of the leakage flow enters the tip honeycomb cavity, forming small-scale vortices and mixes with the upper leakage fluid, which increases the flow resistance within the clearance. In the range of clearance height variation investigated, honeycomb tip structure can effectively reduce the leakage flow, and reduce the size and strength of the leakage vortex, so that the loss of the cascade is reduced. At a large tip clearance height, the unstable split of the vortex cores causes the vortex in the honeycomb cavities near pressure side to grow in size, so that the vortex extends further into the upper gap, where the turbulent blocking effect of the vortices on the leakage flow is increased. However, due to the vortex movement and the mixing between honeycomb vortices and the upper clearance flow, there is no obvious advantage in reducing the total loss of the cascade compared to the small tip clearance height.